Cationic antimicrobial peptides serve as activation signals for the Salmonella Typhimurium PhoPQ and PmrAB regulons in vitro and in vivo - Richards, Susan M.; Strandberg, Kristi L.; Conroy, Megan; Gunn, John S. (Frontiers in Cellular and Infection Microbiology, 2012)
Salmonella enterica serovar Typhimurium uses two-component regulatory systems (TCRSs) to respond to environmental stimuli. Upon infection, the TCRSs PhoP-PhoQ (PhoPQ) and PmrA-PmrB (PmrAB) are activated by environmental signals detected in the lumen of the intestine and within host cells. TCRS-mediated gene expression leads to upregulation of genes involved in lipopolysaccharide (LPS) modification and cationic antimicrobial peptide (CAMP) resistance. This research expands on previous studies which have shown that CAMPs can activate Salmonella TCRSs in vitro. The focus of this work was to determine if CAMPs can act as environmental signals for PhoPQ- and PmrAB-mediated gene expression in vitro, during infection of macrophages and in a mouse model of infection. Monitoring of PhoPQ and PmrAB activation using RIVET, alkaline phosphtase and β-galactosidase reporter fusion constructs demonstrated that S. Typhimurium PhoQ can sense CAMPs in vitro. In mouse macrophages, the cathelecidin CRAMP does not activate the PhoPQ regulon. Acidification of the Salmonella-containing vacuole activates PhoP- and PmrA-regulated loci but blocking acidification still does not reveal a role for CRAMP in TCRS activation in mouse macrophages. However, assays performed in susceptible wild type (WT), CRAMP knockout (KO) and matrilysin (a metalloproteinase necessary for activating murine α-defensins) KO mice suggest CRAMP, but not α-defensins, serve as a putative direct TCRS activation signal in the mouse intestine. These studies provide a better understanding of the in vivo environments that result in activation of these virulence-associated TCRSs.